Financial sustainability in Islamic secondary schools: diversifying financial resources through Islamic social finance mechanisms - Mohd. Zain, Nor Razinah; Md Sidek, Suzana Suhailawaty; Hasbullah, Nurul Fadzlin (NAMA Foundation, 2024)
Islamic secondary schools are non-profit educational institutions that can either be affiliated with governments’ assistantship or depending on self-generated income. Financial sustainability is found to be scarcely discussed in literature review, especially when it is related to Islamic secondary schools. This research identifies the application of financial sustainability in non-profit educational institutions, with a focus on Islamic secondary schools. With the expansion of researches relating to Islamic social finance and mechanisms, this research also explores their potentials in demystifying the financial sources for the Islamic secondary schools which are suitable to allow them to maintain their financial sustainability. It is found that Islamic social finance offers several financing mechanisms that meet Shariah-compliance, philanthropic in nature, and allow participations from the public. These Islamic social finance mechanisms are zakat, sadaqah, waqf, and etc. Additionally, sponsorships can also be received by Islamic secondary schools through institutional grants. Here, examples of practices are traced from reports issued by NAMA Foundation and their contributions towards the selected Islamic secondary schools. With an objective to assist the Islamic secondary schools to achieve their financial sustainability, the researchers suggest a model that integrates Islamic social finance and its suitable mechanisms which may be applied to Islamic secondary schools. Challenges for the application of this model are also highlighted.